What Influenced Generation Z Decision to Enter E-Sport as a Career? - Gozali, Axel; Hansfel, Laurensius; Octaviani, Sarah Nabilla; Murwani, Ina Agustini (Eduvest - Journal of Universal Studies, 2023)
Current technological developments, especially in the gaming industry, have created new job opportunities in digital games and a new phenomenon known as e-sports. There is a relationship between e-sports and career. There is still limited research on e-sports and one's career, especially those related to the variables Self-efficacy, Extrinsic Motivation, Intrinsic Motivation, Influence by Third Parties, and Career Exposure, so this study aims to examine more deeply the relationship between these variables and career choices in the generation-z. Two hundred eighty respondents in the Greater Jakarta area were examined using a judgmental sampling technique. This study uses Smartpls 3.0 to test the hypotheses' validity, reliability, and results. The results of the study state that Self-Efficacy, Extrinsic Motivation, Intrinsic Motivation, and Career Exposure affect Career Choice, while Influence by Third Parties does not affect Career Choice.